Exploring English-Speaking Anxiety Levels and Contributing Factors among Indonesian EFL Undergraduate Students - Kulsum, Eva Meidi; Putri, Rizka Rahil; Sri Widianingsih, Ayang Winda (Communication In Research And Publications, 2025)
This study explores the classification of English-speaking anxiety levels and identifies the underlying factors contributing to speaking anxiety among EFL undergraduate students. A descriptive qualitative approach was employed, using two main instruments: a questionnaire adapted from Horwitz et al.’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) and semi-structured interviews that provided deeper insights into students’ perspectives and experiences. The participants were 24 students from an English Education program. The findings revealed that the majority of students (75%) experienced moderate anxiety, while 16.67% showed low anxiety and 8.33% high anxiety. These outcomes reflect a complex interplay of anxiety dimensions: Fear of Negative Evaluation was the most prominent factor (M = 2.47), followed by Communication Apprehension (M = 2.37), and Test Anxiety as the least influential (M = 2.24). The overall results indicate that speaking anxiety was present but not overwhelmingly severe among participants. The study highlights the importance of understanding both the frequency and sources of anxiety, as such insights can inform strategies to foster supportive and non-judgmental classroom environments. Creating these conditions may encourage students to develop greater confidence, enhance oral performance, and reduce their speaking anxiety in EFL contexts.